2008
DOI: 10.1038/modpathol.3800980
|View full text |Cite
|
Sign up to set email alerts
|

Silent mutations in KIT and PDGFRA and coexpression of receptors with SCF and PDGFA in Merkel cell carcinoma: implications for tyrosine kinase-based tumorigenesis

Abstract: Merkel cell carcinoma is a rare and aggressive form of skin cancer of neuroendocrine origin. Its treatment involves wide excision and radiotherapy but no effective therapy exists for advanced disease. Upregulation of the platelet-derived growth factor receptor family of tyrosine kinases, PDGFRA and KIT, has a crucial role in cancer development. Several studies have shown expression of the tyrosine kinase receptor KIT (CD117) in Merkel cell carcinoma. In this study, we examined the expression and mutational sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 49 publications
5
51
3
Order By: Relevance
“…In addition, we did not detect any mutations in 4 MCC cell lines that contain MCPyV. Consistent with previous studies, we did not find activating muta tions in PDGFRA or KIT (23,(35)(36)(37)(38). We did identify 3 tumors with p53 point substitutions, most notably in 2 specimens with absent expression of MCPyV large T antigen.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we did not detect any mutations in 4 MCC cell lines that contain MCPyV. Consistent with previous studies, we did not find activating muta tions in PDGFRA or KIT (23,(35)(36)(37)(38). We did identify 3 tumors with p53 point substitutions, most notably in 2 specimens with absent expression of MCPyV large T antigen.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, we performed mutational analysis in 51 specimens of these rare neoplasms. The fact that we confirmed several expression patterns that have been previously reported using other subgroups of these rare neoplasms supports the validity of our findings (Kartha and Sundram 2008;Micke et al 2004;Rossi et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…PDGFRA expression was observed in 33% and was also associated with a higher grading (grade 1 in 15%, grade 2 in 42%, and grade 3 in 50%). Similarly, Kartha and Sundram (2008) found a higher incidence of PDGFRA (87%) in Merkel cell carcinomas, a subtype of poorly differentiated neuroendocrine carcinoma of the skin indicating the higher expression of PDGFRA in poorly differentiated tumors is not a rare molecular event. Furthermore, in our study, a coexpression of high KIT and high PDGFRA was found in 95% (P \ 0.001) of our tumors, and high KIT/ PDGFRA expression was significantly correlated with metastases (P \ 0.001).…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that the autocrine stimulation of KIT by SCF may represent a major pathway of KIT activation in this tumor. During preparation of this paper, a recent publication reported co-expression of KIT and SCF in 16% of MCC tumors [27]. That rate is substantially lower than the one seen in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Differences in positivity rates may result from different antibodies and dilutions, antigen retrieval methods or other variations in staining protocols. Nevertheless, due to the rare co-expression of KIT and SCF in MCC in their report and the SCF staining of surrounding connective tissues, Kartha and Sundram [27] rather favor a paracrine mode for KIT activation. In our study, we have also detected SCF in endothelial and smooth muscle cells as well as in sweat glands, but we found no free SCF in the dermis.…”
Section: Discussionmentioning
confidence: 99%